2012
DOI: 10.1007/s10571-012-9837-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Glial Activation in the Hippocampal CA1 Region Between The Young and Adult Gerbils After Transient Cerebral Ischemia

Abstract: It has been reported that young animals are less vulnerable to brain ischemia. In the present study, we compared gliosis in the hippocampal CA1 region of the young gerbil with those in the adult gerbil induced by 5 min of transient cerebral ischemia by immunohistochemistry and western blot for glial cells. We used male gerbils of postnatal month 1 (PM 1) as the young and PM 6 as the adult. Neuronal death in CA1 pyramidal neurons in the adult gerbil occurred at 4 days post-ischemia; the neuronal death in the yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Microglial reactivity in the ischemic brain is closely associated with the development of delayed neuronal cell death in vulnerable regions (4,30). An early and transient microglial reaction occurs throughout the majority of the hippocampus within 24 h of ischemia, including the hippocampal CA3 region, where no subsequent neuronal loss occurs (31).…”
Section: Discussionmentioning
confidence: 99%
“…Microglial reactivity in the ischemic brain is closely associated with the development of delayed neuronal cell death in vulnerable regions (4,30). An early and transient microglial reaction occurs throughout the majority of the hippocampus within 24 h of ischemia, including the hippocampal CA3 region, where no subsequent neuronal loss occurs (31).…”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with our and other previous studies reporting that tFI-induced DND in the hippocampal CA1 in young gerbils was shown in fewer pyramidal neurons and more delayed in time than that shown in adult gerbils ( 9 , 24 , 25 ). Taken together, we suggest that the difference of DND between young and adult groups might be associated with the differences of various factors to affect DND, including glial activation, inflammatory cytokine expression and NMDA receptor expression ( 26 28 ).…”
Section: Discussionmentioning
confidence: 83%
“…In the BBB, extracellular ion and water balance are controlled by various ion and water channels that are expressed in the astrocyte-endfeet [31]. In the case of microglia, they take charge as immunocytes in the CNS and secrete diverse kinds of inflammatory cytokines in specific states such as ischemic insults [32,33]. As immune cells, microglia can remove dead cells and tissue debris in the CNS under pathological conditions [34].…”
Section: Discussionmentioning
confidence: 99%